Kebijakan Pemerintah Daerah dalam Mengatasi Kenaikan Harga Pengan saat Mendekati Hari Raya Idul Fitri: Studi Kasus Kota Tanjung Pina - Fitri Nurzana; Novrianti Novrianti (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
The increase in food prices in the city of Tanjung Pinang has become a regular occurrence every year. When approaching Eid, prices will increase very rapidly because the number of goods demanded continues to increase. Meanwhile, the number of goods remains constant or tends to decrease. However, when Eid or other big holidays do not occur, this research method uses the library research method, namely research carried out using library literature, in the form of books, journals and all forms of writing related to the above. The results of the research are to find out 1. what basic needs are experiencing increases in food prices 2. What factors cause increases in food prices 3. What solutions must be taken to overcome the problem of food increases ahead of Eid.